Mutagenicity, antioxidant activity and nutritional content of long-life tomato (Bioscience Journal, 2016)
The increasing tomato demand for the food market motivates improvements and the use of new biotechnologies in this fruit's production. The hybrid crop stands out for fruit production resistant to rot and postharvest wilt (long-life crops). Within this context, consumption of genetically modified food deserves attention regarding the safety and nutritional aspects due to the fact that inclusion and/or overexpression of genetic traits can cause harm to human health in the short or long term. In this scenario, this study aimed to evaluate genotoxicity and mutagenicity from different varieties of long-life tomatoes obtained by genetic breeding and also determines main bioactive compounds and antioxidant activity. The genotoxicity and mutagenicity were analyzed via the micronucleus test and the evaluation of chromosome aberrations in mice bone marrow respectively. We have also analyzed carotene, beta-carotene, lycopene, total phenol and flavonoid contents via spectrophotometry and antioxidant activity via DPPH radical scavenging assay. Considering the results obtained, it is possible to conclude that despite the absence of significant genotoxic activity among the evaluated samples, the antioxidant activity and the differences found in composition seems to be ruled by genetic factors, possibly due to the genetic breeding.